Lyle finds his mother. - Waber, Bernard (Boston, Houghton Mifflin, 1974)
Lyle the Crocodile leaves his happy home on East 88th Street with the Primms to go in search of his mother at the urging of his former employer Hector P. Valenti, star of stage and screen.
Keywords: Crocodiles -- Fiction